Abrasively resistant low-gas-content copper-chromium contact and method of making same
Patent Information
- Application Number
- CN202410079170.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-18
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-18
AI Technical Summary
[0004]针对上述现有技术制备的铜铬触头耐压、耐烧蚀能力较差,气体含量较高的问题,提供了一种耐烧蚀低气体含量的铜铬触头及其制备方法,本发明制备的铜铬触头具有耐电压等级高、耐腐蚀性好以及气体含量低的优异性能
[0022]本发明通过采用预制低气体含量的铬骨架代替传统的铬块所制备的铜铬触头气体含量更低,在高电压等级下能够大大提高真空开关的绝缘性;本发明在真空熔炼过程中添加微量的钨元素提高了触头的耐压性和抗烧蚀性,本发明制备的触头耐压等级最高达到72.5Kv;本发明制备的铜铬触头致密性高,铜铬25触头、铜铬30触头、铜铬40触头密度分别为8.36-8.39g/cm3、8.29-8.30g/cm3、8.10-8.12g/cm3,对应的致密度分别为98.7%-99.0%、98.8%-98.9%、98.6%-98.8%,接近全致密,大大降低了触头在燃弧过程中的重燃概率;电导率高的触头可以消除真空开关温升效应,本发明制备的铜铬触头硬度和电导率明显也有明显的提高,最高硬度达到85HB,耐压等级最高达到72.5Kv;电导率最高能达到31MS/m,因此,本发明制备的铜铬触头具有低含气量、高耐压和耐烧蚀特性。
Smart Images

Figure CN117904474B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of copper-based composite material preparation technology, to a method for preparing vacuum switch contact materials, and particularly to a copper-chromium contact with low gas content and ablation resistance, and its preparation method. Background Technology
[0002] Copper-chromium contacts possess excellent breaking capacity, good withstand voltage characteristics, good resistance to arc erosion, and resistance to welding. They have been widely used in medium and low-voltage vacuum switches. With the global dual-carbon revolution driving the gradual replacement of 72.5kV, 126kV, and 252kV SF6 high-voltage switches with vacuum switches, high-voltage vacuum switches are expected to develop rapidly. As the core material of vacuum switches, improving the ablation resistance, insulation resistance, and reducing the gas content of copper-chromium contacts are key factors for their successful application in high-voltage vacuum switches.
[0003] Currently, the main processes for preparing copper-chromium contacts include powder metallurgy, vacuum casting, vacuum infiltration, and arc melting. However, the contacts prepared by these processes have the following problems: 1. Poor withstand voltage and ablation resistance. The copper-chromium contacts prepared by the current processes are only suitable for medium and low voltage vacuum switches of 1.2kV-72.5kV. For high voltage vacuum switches with voltage levels greater than 72.5kV, the copper-chromium contacts still have problems with insufficient insulation and severe arc erosion; 2. High gas content. For medium and low voltage vacuum switches, the high gas content has little impact on the withstand voltage of the vacuum switch. However, for high voltage and ultra-high voltage vacuum switches, the high gas content affects the insulation and arc extinguishing ability of the vacuum switch. Summary of the Invention
[0004] To address the problems of poor voltage resistance, ablation resistance, and high gas content in copper-chromium contacts prepared by the prior art, this invention provides a copper-chromium contact with low ablation resistance and low gas content, as well as its preparation method. The copper-chromium contact prepared by this invention has excellent properties such as high voltage resistance, good corrosion resistance, and low gas content.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A method for manufacturing a copper-chromium contact with low gas content and resistance to ablation includes the following steps:
[0007] Carbon powder and chromium powder are dried and then mixed to obtain carbon-containing chromium powder; the carbon-containing chromium powder is degassed and sintered under vacuum to obtain a chromium skeleton.
[0008] Chromium skeleton, oxygen-free copper rod and tungsten powder are mixed in a preset ratio and heated under vacuum. When copper and chromium begin to melt, inert gas is introduced to reach a preset pressure. Heating continues until all copper and chromium are melted. Then the heating power is reduced for refining. The refined melt is then cast to obtain an ingot.
[0009] The ingot is modified, heat-treated, forged and straightened to obtain a bar stock. After heat treatment, the bar stock is cooled to obtain a copper-chromium contact.
[0010] The ratio of carbon powder to chromium powder is 0.2-0.4: 99.8-99.6.
[0011] The chromium powder has a particle size of -80 to +240 mesh; the carbon powder has a particle size of 200 to 300 mesh.
[0012] The carbon-containing chromium powder is degassed and sintered under vacuum to obtain a chromium framework, specifically:
[0013] Carbon-containing chromium powder is placed in an environment with a vacuum degree ≤1x10-2Pa, heated to a preset temperature, and then subjected to heat preservation and degassing treatment.
[0014] After degassing, the temperature is raised to 900℃~960℃ and sintered for 120 minutes to obtain the chromium skeleton.
[0015] The preset ratio, by weight percentage, is 24.5–39.8 wt% : 75–60 wt% : 0.2–0.5 wt% for the chromium skeleton, oxygen-free copper rod, and tungsten powder.
[0016] The process of mixing the chromium skeleton, oxygen-free copper rod, and tungsten powder in a preset ratio and then heating them under vacuum conditions involves starting heating when the vacuum level is ≤1x10-2Pa, with the heating power starting at 10KW and increasing the heating power in a stepwise manner.
[0017] The preset pressure is -0.06 to -0.08 MPa.
[0018] The casting temperature of the melt is related to the chromium content. The casting temperature of copper-chromium 25 material is 1550℃~1600℃; the casting temperature of copper-chromium 30 material is 1600℃~1700℃; and the casting temperature of copper-chromium 40 material is 1750℃~1850℃.
[0019] The refined melt is then cast, and the melt is directionally cooled at 100-350℃ / mm.
[0020] The copper-chromium contacts prepared by the above method include copper-chromium 25 to copper-chromium 40 contacts.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0022] This invention utilizes a pre-fabricated low-gas-content chromium skeleton instead of a traditional chromium block to produce copper-chromium contacts with even lower gas content, significantly improving the insulation of vacuum switches at high voltage levels. The addition of trace amounts of tungsten during the vacuum melting process enhances the contact's voltage resistance and ablation resistance; the highest voltage resistance rating achieved by this invention is 72.5 kV. Furthermore, the copper-chromium contacts produced by this invention exhibit high density, with densities of 8.36-8.39 g / cm³ for copper-chromium 25, 30, and 40 contacts, respectively. 3 8.29-8.30 g / cm³ 3 8.10-8.12 g / cm³ 3 The corresponding densities are 98.7%-99.0%, 98.8%-98.9%, and 98.6%-98.8%, respectively, which are close to full density, greatly reducing the probability of reignition of the contact during the arcing process. The high conductivity of the contact can eliminate the temperature rise effect of the vacuum switch. The hardness and conductivity of the copper-chromium contact prepared by this invention are also significantly improved, with the highest hardness reaching 85HB and the highest withstand voltage reaching 72.5Kv. The highest conductivity can reach 31MS / m. Therefore, the copper-chromium contact prepared by this invention has low gas content, high withstand voltage and ablation resistance. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly described below:
[0024] Figure 1 This is a flowchart of the method for preparing the copper-chromium contact of the present invention. Detailed Implementation
[0025] Copper-chromium (CCI) electrical contacts are widely used in medium- and low-voltage vacuum switches due to their excellent breaking capacity, withstand voltage characteristics, and good resistance to arc erosion and welding. However, for vacuum switches with voltage levels ≥40.5kV, CCI contacts require low gas content and high withstand voltage and ablation resistance. Currently, contacts prepared using conventional CCI methods suffer from high gas content and poor withstand voltage and ablation resistance.
[0026] To prepare copper-chromium contacts with low gas content and high pressure and corrosion resistance, this invention first prepares a chromium skeleton from chromium powder in a vacuum sintering furnace. Then, in a vacuum induction melting furnace, the chromium skeleton, oxygen-free copper rod, and trace amounts of tungsten powder are melted into an alloyed liquid phase. Finally, the liquid metal is cast into a water-cooled mold for rapid cooling and crystallization to form an ingot. The ingot is then forged, heat-treated, and processed into a copper-chromium contact with low gas content and ablation resistance. The contacts prepared by this invention using a vacuum sintering + vacuum casting method not only have low gas content but also good pressure resistance.
[0027] This invention discloses a method for preparing an ablation-resistant copper-chromium contact with low gas content, comprising the following steps:
[0028] Materials preparation: Chromium powder: purity ≥99.50%, particle size -80 to +240 mesh; Carbon powder: purity ≥99.5%, particle size 200 to 300 mesh; Oxygen-free copper rod: Cu+Ag ≥99.70%, the surface of the oxygen-free copper rod is free of oil stains, electrolytic residues and oxidation; Tungsten powder: purity ≥99.5%, particle size 325 mesh.
[0029] The prefabrication of a low-gas-content chromium skeleton includes mixing, charging, and sintering processes, with the specific steps as follows:
[0030] Mixing: First, mix carbon powder and chromium powder in a ratio of 0.2-0.4:99.8-99.6, then place them in a vacuum oven at 60-80℃ for 6 hours, and finally mix them in a mixer for 1-3 hours to obtain carbon-containing chromium powder.
[0031] Loading: The carbon-containing chromium powder is loaded into the graphite crucible and compacted by vibration. Then the graphite crucible is placed in a vacuum sintering furnace.
[0032] Sintering: Sequentially turn on the mechanical pump, Roots pump, and diffusion pump to evacuate the vacuum until the vacuum level is ≤1x10⁻¹. -2 Heating begins at Pa, and the temperature is raised to 700℃. After holding at this temperature for 120 minutes for degassing, the temperature is then raised to 900℃~960℃ and held for 120 minutes for sintering to obtain the chromium skeleton.
[0033] The weight percentages of the chromium skeleton, oxygen-free copper rod, and tungsten powder are 24.5–39.8 wt% : 75–60 wt% : 0.2–0.5 wt%. The chromium skeleton, oxygen-free copper rod, and tungsten powder are mixed in this ratio, and the prepared mixture is loaded into a calcium oxide crucible in the induction furnace. A vacuum is then applied to ensure the vacuum level inside the induction furnace is ≤1 x 10⁻⁶. -2Heating begins after Pa; the heating power is increased stepwise from 10KW every 10 minutes by 10KW. When copper and chromium begin to melt, high-purity inert gas (≥99.999%) is introduced until the pressure inside the induction furnace reaches -0.06-0.08MPa, at which point the gas supply is stopped. The heating power is increased until the copper and chromium are completely melted, then the power is reduced to 10KW. After refining for another 10-15 minutes, the melt is quickly poured into a water-cooled mold to obtain an ingot. The casting temperature of the melt is related to the chromium content. The casting temperature of copper-chromium 25 material is 1550℃-1600℃; the casting temperature of copper-chromium 30 material is 1600℃-1700℃; and the casting temperature of copper-chromium 40 material is 1750℃-1850℃. When the casting speed is controlled to keep the liquid height 5mm-20mm above the solidified ingot, and the water pressure of the water-cooling mold is 0.3MPa-0.4MPa, and the return water temperature is ≤35℃, the melt will be directionally cooled at a temperature of 100-350℃ / mm in the water-cooling mold. This prevents large-scale segregation of chromium during the crystallization process.
[0034] The riser and bottom surface of the ingot are sawed off. The riser is sawed until there are no shrinkage cavities, and the bottom surface is sawed off by 5-10mm. Then the ingot is heated to 900℃-950℃ and forged using a sieve. After forging to the specified size, the bar stock is straightened.
[0035] The bar stock was heat-treated in a pit-type heat treatment furnace at a temperature of 750℃ for 240 minutes, and then naturally cooled with the furnace to obtain a copper-chromium contact material with low gas content and resistance to ablation.
[0036] The present invention uses the above-described preparation method to prepare copper-chromium 25 to copper-chromium 40 contacts.
[0037] In the following embodiments, unless otherwise specified, all materials used can be obtained through ordinary channels; the testing methods used are conventional methods in the art; among them, copper powder was purchased from Chongqing GRINM Heavy Metallurgy New Materials Co., Ltd., batch number: 237-282; chromium powder was purchased from Zhonghong, batch number: 230719-01; oxygen-free copper rod was purchased from Jinchuan, batch number: 230716-32-2.
[0038] The following raw materials were used in all examples: Chromium powder: purity ≥ 99.50%, particle size -80 to +240 mesh; Carbon powder: purity ≥ 99.5%, particle size 200 to 300 mesh; Oxygen-free copper rod: Cu+Ag ≥ 99.70%, the surface of the oxygen-free copper rod is free of oil stains, electrolytic residues and oxidation phenomena; Tungsten powder: purity ≥ 99.5%, particle size 325 mesh.
[0039] Example 1: Preparation of Copper Chromium 25 Contacts
[0040] A mixture of 99.8 wt% chromium powder and 0.2 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 60°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0041] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with an amplitude of 0.5 mm; then it was placed in a vacuum sintering furnace with a vacuum degree of 2.2 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 900°C and held for 120 minutes to sinter a chromium skeleton.
[0042] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 24.8 wt% : 75 wt% : 0.2 wt%, and the mixed material was placed into a calcium oxide crucible in the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.5 x 10⁻⁶. -3 Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes. When copper and chromium begin to melt, argon gas is introduced until the pressure inside the induction furnace reaches -0.06MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW, and the furnace is refined for another 10 minutes. When the melt temperature reaches 1550℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained at 5mm-10mm above the solidified ingot. The water pressure of the water-cooled mold is 0.3MPa, and the return water temperature is 25℃ to obtain the ingot.
[0043] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 25 contacts.
[0044] The prepared copper-chromium 25 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0045] Example 2: Preparation of Copper Chromium 25 Contacts
[0046] A mixture of 99.7 wt% chromium powder and 0.3 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 80°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0047] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with a 0.5 mm amplitude; then it was placed in a vacuum sintering furnace with a vacuum degree of 1.8 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 930°C and held for 120 minutes to sinter a chromium skeleton.
[0048] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 24.7 wt% : 75 wt% : 0.3 wt%, and the mixed material was placed into a calcium oxide crucible in the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.3 x 10⁻⁶. -3 Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes by 10KW. When copper and chromium begin to melt, argon gas is introduced until the pressure inside the induction furnace reaches -0.07MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW and refined for another 12 minutes. When the melt temperature reaches 1580℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained at 5mm-10mm above the solidified ingot. The water pressure of the water-cooled mold is 0.4MPa, and the return water temperature is 25℃ to obtain the ingot.
[0049] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 25 contacts.
[0050] The prepared copper-chromium 25 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0051] Example 3: Preparation of Copper Chromium 25 Contacts
[0052] A mixture of 99.6 wt% chromium powder and 0.4 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 80°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0053] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with an amplitude of 0.5 mm; then it was placed in a vacuum sintering furnace with a vacuum degree of 1.1 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 960°C and held for 120 minutes to sinter a chromium skeleton.
[0054] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 24.5 wt% : 75 wt% : 0.5 wt%, and the mixed material was placed into the calcium oxide crucible of the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.3 x 10⁻⁶. -3 Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes by 10KW. When copper and chromium begin to melt, argon gas is introduced until the pressure inside the induction furnace reaches -0.08MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW and refined for another 15 minutes. When the melt temperature reaches 1600℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained at 5mm-10mm above the solidified ingot. The water pressure of the water-cooled mold is 0.4MPa, and the return water temperature is 25℃ to obtain the ingot.
[0055] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 25 contacts.
[0056] The prepared copper-chromium 25 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0057] Example 4: Preparation of Copper Chromium 30 Contacts
[0058] A mixture of 99.8 wt% chromium powder and 0.2 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 60°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0059] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with a 0.5 mm amplitude; then it was placed in a vacuum sintering furnace with a vacuum degree of 2.5 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 900°C and held for 120 minutes to sinter a chromium skeleton.
[0060] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 29.8 wt% : 70 wt% : 0.2 wt%, and the mixed material was placed into the calcium oxide crucible of the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 2.1 x 10⁻⁶. -3Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes. When copper and chromium begin to melt, argon gas is introduced until the pressure inside the induction furnace reaches -0.06MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW, and the furnace is refined for another 10 minutes. When the melt temperature reaches 1600℃, casting is performed. The casting speed is controlled so that the liquid height is maintained at 5mm-10mm above the solidified ingot. The water pressure of the water-cooled mold is 0.3MPa, and the return water temperature is 25℃ to obtain the ingot.
[0061] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 30 contacts.
[0062] The prepared copper-chromium 30 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0063] Example 4: Preparation of Copper Chromium 30 Contacts
[0064] A mixture of 99.7 wt% chromium powder and 0.3 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 60°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0065] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with an amplitude of 0.5 mm; then it was placed in a vacuum sintering furnace with a vacuum degree of 1.9 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 930°C and held for 120 minutes to sinter a chromium skeleton.
[0066] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 29.7 wt% : 70 wt% : 0.3 wt%, and the mixed material was placed into the calcium oxide crucible of the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.5 x 10⁻⁶. -3Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes. When copper and chromium begin to melt, nitrogen is introduced until the pressure inside the induction furnace reaches -0.07MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW and refined for another 12 minutes. When the melt temperature reaches 1650℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained 5mm-10mm above the solidified ingot. The water pressure of the water-cooled mold is 0.3MPa, and the return water temperature is 25℃ to obtain the ingot.
[0067] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 30 contacts.
[0068] The prepared copper-chromium 30 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0069] Example 5: Preparation of Copper Chromium 30 Contacts
[0070] A mixture of 99.7 wt% chromium powder and 0.3 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 60°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0071] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with an amplitude of 0.5 mm; then it was placed in a vacuum sintering furnace with a vacuum degree of 1.9 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 930°C and held for 120 minutes to sinter a chromium skeleton.
[0072] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 29.7 wt% : 70 wt% : 0.3 wt%, and the mixed material was placed into the calcium oxide crucible of the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.5 x 10⁻⁶. -3Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes. When copper and chromium begin to melt, nitrogen is introduced until the pressure inside the induction furnace reaches -0.07MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW and refined for another 12 minutes. When the melt temperature reaches 1650℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained 5mm-10mm above the solidified ingot. The water pressure of the water-cooled mold is 0.3MPa, and the return water temperature is 25℃ to obtain the ingot.
[0073] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 30 contacts.
[0074] The prepared copper-chromium 30 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0075] Example 6: Preparation of Copper Chromium 30 Contacts
[0076] A mixture of 99.6 wt% chromium powder and 0.4 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 80°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0077] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with an amplitude of 0.5 mm; then it was placed in a vacuum sintering furnace with a vacuum degree of 1.0 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 960°C and held for 120 minutes to sinter a chromium skeleton.
[0078] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 29.5 wt% : 70 wt% : 0.5 wt%, and the mixed material was placed into a calcium oxide crucible in the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.2 x 10⁻⁶. -3Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes. When copper and chromium begin to melt, nitrogen is introduced until the pressure inside the induction furnace reaches -0.08MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW, and the furnace is refined for another 15 minutes. When the melt temperature reaches 1700℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained 5mm-10mm above the solidified ingot. The water pressure of the water-cooled mold is 0.4MPa, and the return water temperature is 25℃ to obtain the ingot.
[0079] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 30 contacts.
[0080] The prepared copper-chromium 30 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0081] Example 7: Preparation of Copper Chromium 40 Contacts
[0082] A mixture of 99.8 wt% chromium powder and 0.2 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 60°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0083] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with an amplitude of 0.5 mm; then it was placed in a vacuum sintering furnace with a vacuum degree of 2.0 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 900°C and held for 120 minutes to sinter a chromium skeleton.
[0084] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 39.8 wt% : 60 wt% : 0.2 wt%, and the mixed material was placed into the calcium oxide crucible of the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 2.3 x 10⁻⁶. -3Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes. When copper and chromium begin to melt, nitrogen is introduced until the pressure inside the induction furnace reaches -0.06MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW and refined for another 10 minutes. When the melt temperature reaches 1750℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained 10mm-20mm above the solidified ingot. The water pressure of the water-cooled mold is 0.3MPa, and the return water temperature is 25℃ to obtain the ingot.
[0085] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 40 contacts.
[0086] The prepared copper-chromium 40 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0087] Example 8: Preparation of Copper Chromium 40 Contacts
[0088] A mixture of 99.7 wt% chromium powder and 0.3 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 60°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0089] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with a 0.5 mm amplitude; then it was placed in a vacuum sintering furnace with a vacuum degree of 1.6 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 930°C and held for 120 minutes to sinter a chromium skeleton.
[0090] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 39.7 wt% : 60 wt% : 0.3 wt%, and the mixed material was placed into a calcium oxide crucible in the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.3 x 10⁻⁶. -3Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes by 10KW. When copper and chromium begin to melt, nitrogen is introduced until the pressure inside the induction furnace reaches -0.07MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW and refined for another 12 minutes. When the melt temperature reaches 1800℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained 10mm-20mm above the solidified ingot. The water pressure of the water-cooled mold is 0.3MPa, and the return water temperature is 25℃ to obtain the ingot.
[0091] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 40 contacts.
[0092] The prepared copper-chromium 40 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0093] Example 9: Preparation of Copper Chromium 40 Contacts
[0094] A mixture of 99.6 wt% chromium powder and 0.4 wt% carbon powder was prepared by weight percentage. The mixture was dried in a vacuum drying oven at 60°C for 6 hours. The dried mixture was then loaded into a mixer for mixing for 3 hours to obtain carbon-containing chromium powder.
[0095] Carbon chromium powder is loaded into a container with a specification of The crucible was compacted for 30 seconds using a vibrating mill with an amplitude of 0.5 mm; then it was placed in a vacuum sintering furnace with a vacuum degree of 1.2 x 10⁻⁶. -3 The temperature was initially set at Pa, then increased to 700°C in 120 minutes and held for 120 minutes for degassing. The temperature was then raised to 960°C and held for 120 minutes to sinter a chromium skeleton.
[0096] The chromium skeleton, oxygen-free copper rod, and tungsten powder were mixed in a weight percentage ratio of 39.5 wt% : 60 wt% : 0.5 wt%, and the mixed material was placed into the calcium oxide crucible of the induction furnace. A vacuum was then created inside the induction furnace to achieve a vacuum level of 1.1 x 10⁻⁶. -3Heating begins at Pa, with the heating power increasing in stages from 10KW every 10 minutes. When copper and chromium begin to melt, nitrogen is introduced until the pressure inside the induction furnace reaches -0.08MPa. The heating power is then increased until the copper and chromium are completely melted. The power is then reduced to 10KW and refined for another 15 minutes. When the melt temperature reaches 1850℃, casting is carried out. The casting speed is controlled so that the liquid height is maintained 10mm-20mm above the solidified ingot. The water pressure of the water-cooled mold is 0.3MPa, and the return water temperature is 25℃ to obtain the ingot.
[0097] The riser of the ingot is sawn until there are no shrinkage cavities, and 8mm is sawn off the bottom surface. Then the ingot is heated to 900℃ and die-forged using a sieve. After die-forging to the specified size bar, it is straightened. Then the bar is heat-treated in a pit-type heat treatment furnace at 750℃ for 240 minutes. It is then cooled naturally in the furnace to obtain copper-chromium 40 contacts.
[0098] The prepared copper-chromium 40 contacts were tested for relevant properties, and the test results are shown in Table 1.
[0099] Table 1. Comparison of the performance of copper-chromium contacts prepared by the present invention with that of contacts prepared by existing technologies.
[0100]
[0101]
[0102] The material performance parameters in Table 1, prepared using existing technologies, are derived from the national standard GB / T26867—2011, which outlines the technical requirements for copper-chromium electrical contacts.
[0103] As shown in Table 1, the gas content and ablation depth of the copper-chromium 25, copper-chromium 30, and copper-chromium 40 contacts prepared by this invention are significantly lower than those prepared by existing technologies; the minimum ablation depth after 30 breaks is only 1.0 mm; the density, hardness, conductivity, and withstand voltage rating of the contacts prepared by this invention are significantly higher than those prepared by traditional technologies, with densities of 8.36-8.39 g / cm³ for the copper-chromium 25, copper-chromium 30, and copper-chromium 40 contacts, respectively. 3 8.29-8.30 g / cm³ 3 8.10-8.12 g / cm³ 3 The corresponding densities are 98.7%-99.0%, 98.8%-98.9%, and 98.6%-98.8%, respectively, which are close to full density, greatly reducing the probability of reignition of the contact during the arcing process; high hardness indicates good density of the contact material and high pressure resistance, with the highest contact hardness reaching 85HB and the highest pressure resistance reaching 72.5Kv; therefore, the copper-chromium contact prepared by this invention has low gas content, high pressure resistance and ablation resistance characteristics.
[0104] The above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still make modifications or equivalent substitutions to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the protection scope of the claims of the present invention pending approval.
Claims
1. A method for manufacturing a copper-chromium contact with low gas content and resistance to ablation, characterized in that, Includes the following steps: Carbon powder and chromium powder are dried and then mixed to obtain carbon-containing chromium powder; the carbon-containing chromium powder is placed under a vacuum of ≤1x10⁻⁶. -2 In an environment of Pa, the mixture is heated to a preset temperature and subjected to heat preservation and degassing treatment; after degassing treatment, the temperature is raised to 900℃~960℃ and sintered for 120 minutes to obtain a chromium skeleton; the ratio of carbon powder to chromium powder is 0.2~0.4∶99.8~99.6; After mixing the chromium skeleton, oxygen-free copper rod, and tungsten powder in a predetermined ratio, the mixture is subjected to a vacuum degree ≤1x10⁻⁶. -2 Heating begins at a pressure of 10 kW, with the heating power increasing in stages. When copper and chromium begin to melt, inert gas is introduced to reach the preset pressure. Heating continues until all copper and chromium are melted. Then, the heating power is reduced for refining. The refined melt is then cast to obtain an ingot. The preset ratio, by weight percentage, is 24.5~39.8 wt% : 75~60 wt% : 0.2~0.5 wt% for the chromium skeleton, oxygen-free copper rod, and tungsten powder; the preset pressure is -0.06~-0.08 MPa. The ingot is modified, heat-treated, forged and straightened to obtain a bar stock. After heat treatment, the bar stock is cooled to obtain a copper-chromium contact.
2. The method for manufacturing a copper-chromium contact with low gas content and resistant to ablation according to claim 1, characterized in that, The chromium powder has a particle size of -80 to +240 mesh; the carbon powder has a particle size of 200 to 300 mesh.
3. The method for manufacturing a copper-chromium contact with low gas content and resistant to ablation according to claim 1, characterized in that, The casting temperature of the melt is related to the chromium content. The casting temperature of copper-chromium 25 material is 1550℃~1600℃; the casting temperature of copper-chromium 30 material is 1600℃~1700℃; and the casting temperature of copper-chromium 40 material is 1750℃~1850℃.
4. The method for manufacturing a copper-chromium contact with low gas content and resistant to ablation according to claim 1, characterized in that, The refined melt is then cast, and the melt is directionally cooled at 100-350℃ / mm.
5. A copper-chromium contact manufactured using the method described in any one of claims 1 to 4, characterized in that, Including copper-chromium 25~copper-chromium 40 contacts.
Citation Information
Patent Citations
Process for manufacturing countact material for vacuum circuit breakers
CN1068597A
Contact material for vaccum valves and manufacturing process
CN87100389A
Method of producing copper-chromium fusion alloys as contact material for vacuum power switches
US4537745A